Relationship Between Age and Lexical Access - Issa, Saddam; Alfarhan, Abdulah; Awadh, Fares; Aradhya , Abhishek (East European Journal of Psycholinguistics, 2022)
Lexical access refers to the retrieval of the word considered to be appropriate from the lexicon. The related lexical items are assumed to be arranged in a specific pattern. When the related items are presented in succession, it may evoke facilitation or inhibition. When one lexical item facilitates the activation of other lexical items, the term facilitation is used. On the other hand, if one lexical item impedes the lexical activation of the other lexical items, the term inhibition is used. The study aimed to explore lexical-semantic activation patterns in younger and older adults. Continuous naming paradigm was employed to probe the lexical-semantic activation. 40 participants in the age range of 18-25 years; 40 individuals in the age range of 55-70 years served as participants after informed consent. The participants were divided into two groups based on age and they were asked to name pictures. A total of 120 pictures were used (60 related pictures and 60 unrelated pictures were used.). The stimulus was presented in 6 blocks. Each block had 10 semantically related pictures and 10 semantically unrelated pictures. The reaction time and accuracy of scores for related and unrelated pictures did not show statistically significant differences for younger individuals. A statistically significant difference between related and unrelated pictures was seen for older individuals, the reaction time was slower and accuracy was poorer for semantically related pictures. Greater reaction time and poor accuracy scores on semantically related pictures in this group suggested inhibition.